Further steps in the conservation of the kurgans - Rákóczi, Attila (JOURNAL OF LANDSCAPE ECOLOGY, 2018)
Common Agricultural Policy has gone through many reforms since it was established. In 2010, the payable agricultural support was tied to the requirement of protecting the area's characteristic elements. At this time the protection of the mounds was introduced into the requirement system of cross-compliance. I began my doctorate research in 2010 and tracked the condition change of 185 mounds in Békés county via field-walking and monitoring until 2015. My results show that community regulation has provided the mounds with protection more effective than ever before, as at the end of my research only 8 of the 185 mounds remained under cultivation. In this paper I have, after three years, examined the state of the county's mounds via field-walking in search of changes. In the past years, I have made recommendations to the settlement securities depository board to increase the protection of certain mounds. The county government office has begun the entry of these mounds into the land registry. It has been determined that none of the mounds that were previously left have been placed under cultivation again, and of the 8 mounds that were cultivated in 2015, 3 have ceased to be disturbed. The securities depositories of the affected settlements have accepted 10 of the municipal securities depository propositions, and 82 mounds were registered officially in the real estate registry. On the whole, we can determine that the present measures and processes will guarantee that the mounds will be preserved for posterity.
Keywords: common agricultural policy; cross compliance; nature conservation; kurgan